2013
DOI: 10.1159/000351948
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Radical Prostatectomy for the Treatment of Radiation-Resistant Prostate Cancer: Surgical, Oncological and Short-Term Functional Outcomes

Abstract: Objective: The objective of this study was to assess the surgical, oncological and short-term functional outcomes in patients undergoing salvage robot-assisted radical prostatectomy (SRARP) for the treatment of radiation-resistant prostate cancer. Patients and Methods: The records of 3,500 men who underwent RARP from February 2006 to July 2011 were retrospectively reviewed. All peri- and postoperative data were recorded prospectively in our database. A total of 13 patients (0.37%) who had undergone SRARP for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 29 publications
(57 reference statements)
2
7
0
Order By: Relevance
“…The lower reported rates of BL in the last series were caused by the presence in the review of two series of robotic SRP [46,52,53]. The average rates of reported rectal injury, anastomotic stricture, and incontinence were 6.8, 18.3, and 47.8%, respectively.…”
Section: Salvage Radical Prostatectomymentioning
confidence: 99%
See 1 more Smart Citation
“…The lower reported rates of BL in the last series were caused by the presence in the review of two series of robotic SRP [46,52,53]. The average rates of reported rectal injury, anastomotic stricture, and incontinence were 6.8, 18.3, and 47.8%, respectively.…”
Section: Salvage Radical Prostatectomymentioning
confidence: 99%
“…Moreover, it is also a ‘land of conquest' for minimally invasive approaches, e.g. robotic SRP [53,54]. …”
Section: Salvage Radical Prostatectomymentioning
confidence: 99%
“…At 12 months, 7 patients were continent (53.8%), and 3 patients (23.1%) were potent. During the follow-up period, only 3 patients (23.1%) exhibited BCR [31]. …”
Section: Robot-assisted Radical Prostatectomy After Radiation Failurementioning
confidence: 99%
“…For example, in the Vanderbilt University cohort that included 34 men who underwent sRARP without the use of the scaffold the rate of anastomotic leak was lower than 15% ( 7 ). Similarly, Yuh et al ( 8 ) and Zugor et al ( 9 ) reported that the proportion of men who experienced anastomotic leaks after sRARP without the use of a scaffolding tissue graft for radio-recurrent PCa did not exceed 20%. This is substantially lower as compared to what reported by Ogaya-Pinies and colleagues in their control group, where more than one out of three patients experienced anastomotic leak after surgery.…”
mentioning
confidence: 90%